Telenovelas and attitudes toward the LGBTIQ+ community in Latin America - Selim Gulesci; María Lombardi; Alejandra Ramos (Inter-American Development Bank (IDB), 2023)
How does exposure to soap operas with LGBTIQ+ characters affect attitudes toward the LGBTIQ+ community? To answer this question, we construct a novel database of 175 telenovelas (soap operas) with LGBTIQ+ characters airing in 14 countries in Latin America and the Caribbean between 2002 and 2019. Exploiting variation in the introduction of new soap operas with LGBTIQ+ characters within country and surveywaves, we find that individuals exposed to more soap operas with LGBTIQ+ characters are less tolerant toward the LGBTIQ+ community. This short-term backlash is driven by exposure to telenovelas with homosexual characters and shows with comedic storylines. The effect is stronger among traditionally more conservative individuals (e.g., older or frequently attending religious services).
Keywords: J15; J71; N16; 330; Discrimination; Attitudes; LGBTIQ+; Media; Latin America; Caribbean